Мегаполісна і регіональна ідентичність у діаспорі (дослідження етнічної підгрупи поляків-підгалян в Америці) - Бжозовська-Крайка, А. (Народна творчість та етнологія, 2012)
Anna Brzozowska-Krajka. Metropolitan and Regional Identity in Diaspora (the Сase Study of Ethnic Subgroup of Polish Highlanders in America). The article addresses issues related to the cultural identity of contemporary Chicago Polonia of Highlander origin. I focus on two dimensions of this cultural identity: metropolitan (global, related to the receiving society, so-called mainstream Americans) and regional (the ethnic minority with a clearly defined private homeland synonymous with the country of origin). As an analytical tool I use Laurу Grossberg’s notion of a mattering map defined as a set of sites and cultural practices that contribute to the emergence of metropolitan or regional identification; an emphasis is put on the ecological aspect of identity (oikos is the Greek word meaning home, environment; in the context of the article, for an individual it is the family home located in South Chicago and for the group it is Polish Highlander Community Center, a secular temple of the highlander culture of «American Podhale»).
The reflections on identity are put into the diachronic context (references to the cultural past, concern for the present, and simultaneous looking into the future – the channels of intergenerational transmission) which allows creating the identification profiles peculiar to the ethnic subgroup under investigation. Whereas the global profile remains marginal the regional-religious (or religious-regional) profile prevails; one may also distinguish the national-regional-religious profile. These forms of cultural expression – of ethnic and global character – allow us to make generalizations about assimilation processes.